Decolonial History teachers’ charter: A praxis guide (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
The below text is a practical charter which calls for history teachers, students, learners and then the provincial and national Departments of Basic and Higher Education to decolonise. Decolonisation is often talked about in the abstract, it is separated out into curricula, pedagogy, or university spaces. This charter takes the argument into schools and explores several aspects of decolonisation in a substantial and detailed way. The charter was developed as a collective exercise in a history methodology class by third and fourth year Bachelor of Education students training to be histori(an) teachers. The idea from the charter emanated from the students, and was initially, pre-Covid, guided by the lecturer (see footnote 1); however, once Emergency Remote Teaching (ERT) began, the students took complete ownership of the project. The lecturer’s only role was to make the charter an assignment, to give students impetus to carry on with the task. Students could work collectively on the Decolonial History Teacher’s Charter, or work on and submit individual assignments. This is important because the desire, the heart, the intellectual work, and the collectivity all emanated from the students. The below document can serve, in our collective view, as an important guide to new and serving history teachers, students, learners, and scholars.
Keywords: History teachers; History students; History teaching; Decolonisation; Praxis